2021
DOI: 10.1002/jbt.22836
|View full text |Cite
|
Sign up to set email alerts
|

The hepatoprotective potential of resveratrol in an experimental model of ruptured abdominal aortic aneurysm via oxidative stress and apoptosis

Abstract: The mortality rate in ruptured abdominal aortic aneurysms can today be reduced through cardiovascular surgery. However, ischemia and reperfusion‐induced tissue damage develop due to aortic cross‐clamping applied during surgery. The present study aimed to reduce oxidative stress‐induced hepatic damage resulting from ischemia and reperfusion due to aortic cross‐clamping during surgery by means of resveratrol administration. Forty male Sprague–Dawley rats were randomly assigned into four groups: control (healthy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Results of a previous study demonstrated that RSV may decrease the levels of peroxylipids, increase the activity of SOD and reduce the water content in rat brain tissues subjected to cerebral I/R, demonstrating a positive protective effect on cerebral I/R injury [31]. RSV administration also reduced the levels of cleaved caspase-3 and MDA, suggesting that RSV may be effective against liver I/R injury by reducing oxidative stress and apoptosis [32]. In addition, RSV demonstrated strong cardio-protective and anti-PLOS ONE arrhythmic effects following myocardial I/R, as indicated by the levels of CAT, SOD, MDA and glutathione peroxidase [33].…”
Section: Discussionmentioning
confidence: 91%
“…Results of a previous study demonstrated that RSV may decrease the levels of peroxylipids, increase the activity of SOD and reduce the water content in rat brain tissues subjected to cerebral I/R, demonstrating a positive protective effect on cerebral I/R injury [31]. RSV administration also reduced the levels of cleaved caspase-3 and MDA, suggesting that RSV may be effective against liver I/R injury by reducing oxidative stress and apoptosis [32]. In addition, RSV demonstrated strong cardio-protective and anti-PLOS ONE arrhythmic effects following myocardial I/R, as indicated by the levels of CAT, SOD, MDA and glutathione peroxidase [33].…”
Section: Discussionmentioning
confidence: 91%
“…to remove excessive ROS and reducing mitochondrial damage to protect cellular senescence and AAA (136,137). In addition, mdivi1, an inhibitor of Drp1, can also effectively maintain mitochondrial integrity and reduce vascular senescence (132,138).…”
Section: Mitochondrial Dysfunction-related Senescence and Abdominal A...mentioning
confidence: 99%
“…The therapies that improve mitochondrial function by exogenous supplementation of their precursors, such as nicotinamide riboside (NR) and nicotinamide mononucleotide (NMN), have been demonstrated to be effective in the treatment of CVDs in vivo experiments ( 134 , 135 ). The natural compound resveratrol not only acts as an activator of SIRT1, but also acts as an antioxidant, helping to remove excessive ROS and reducing mitochondrial damage to protect cellular senescence and AAA ( 136 , 137 ). In addition, mdivi1, an inhibitor of Drp1, can also effectively maintain mitochondrial integrity and reduce vascular senescence ( 132 , 138 ).…”
Section: Evidence and Mechanisms Of Cellular Senescence In Abdominal ...mentioning
confidence: 99%
“…No marked improvement has still been achieved in mortality rates in rAAA, which remains an important cause of mortality in men over 65 years old [ 1 ] . Also considering those patients who die with correct diagnoses before reaching the cardiovascular surgery team, rAAA is a much more important health problem than currently believed [ 2 ] . In rAAA, hypovolemic shock, which usually develops due to bleeding from the retroperitoneum, and sometimes into the abdomen, causes widespread perfusion disturbance in the entire body.…”
Section: Introductionmentioning
confidence: 99%
“…The essential mechanisms of IRI are free oxygen radical (FOR) formation, a decrease in antioxidant enzymes, lipid peroxidation, neutrophil activation, and caspase-3-induced apoptosis. Myocardial injury caused by IRI is one of the main causes of death in the early postoperative period in patients undergoing rAAA surgery [ 2 , 3 ] . It has been suggested that a significant proportion of problems emerging during intensive care follow-up immediately after surgery develop due to myocardial dysfunction and that myocardial functions, therefore, need to be preserved for recovery [ 3 ] .…”
Section: Introductionmentioning
confidence: 99%